AN EMPIRICAL INVESTIGATION OF CAREER OPTIMISM AMONG TURKISH UNIVERSITY STUDENTS - Muceldili, Busra; Ertosun, Oznur Gulen; Erdil, Oya (Future Acad, 2017)
With the increasing popularity of positive psychology movement in the literature, optimism has attracted many researchers from a various field; however, career optimism has rarely been indicated in the organizational behaviour and human resource management literature. Career optimism, as a part of career planning attitude, is an important factor for career decision making which is a complex process. Indeed, we know little about what career optimism is, its antecedents and consequence in career decision making process among university students. In this study, we empirically demonstrated the relationship among emotional support, task performance, exhaustion at schoolwork and career optimism. By investigating 324 university students (age between 18 and 21) in Turkey, we found that parental emotional support and perceived task performance influences career optimism positively. We also found that exhaustion at schoolwork does not have a significant effect on career optimism. In this regard, theoretical and managerial implications of the study findings are discussed. (C) 2017 Published by Future Academy www.FutureAcademy.org.UK
13th International Strategic Management Conference (ISMC) -- JUL 06-08, 2017 -- Podgorica, MONTENEGRO
Keywords: Career Optimism; Task Performance; Exhaustion at School Work; Parental Emotional Support